Influence of Russian propaganda on German citizens' perception of Russia's war against Ukraine - Kolmakova, Adel (2024)
This study investigates the influence of Russian propaganda on German citizens' perceptions of Russia's war against Ukraine. Through a comprehensive literature review and empirical research involving interviews with 85 German citizens, the thesis examines the primary methods of Russian propaganda dissemination in Germany and assesses its impact on public opinion. The research finds that while Russian propaganda employs various sophisticated techniques, including disinformation campaigns and manipulation of existing social tensions, its overall influence on German public opinion regarding the war appears limited. The majority of respondents demonstrated resistance to pro-Russian narratives, with most supporting Ukraine and recognizing Russia as the aggressor. However, a small segment of the population remains susceptible to Russian propaganda, particularly regarding issues of economic consequences and fears of escalation. The study concludes that while Russian propaganda efforts persist, they have not significantly swayed German public opinion on the war in Ukraine, highlighting the importance of media literacy and critical information consumption in democratic societies.